Gloss to the Supreme Court’s decision of 15 June 2022, II CSKP 509/22 - Rzewuski, Maciej (Review of European and Comparative Law, 2022)
This paper is an attempt at a polemic with the position of the Supreme Court expressed in the cassation case II CSKP 509/22. The subject matter discussed in the paper is of great importance, particularly from a practical point of view, and concerns the issue of the (im)possibility of establishing the date of a will in a situation where doubts arise as to the relation of this will to another will which is dated. The considerations take into account not only the achievements of Polish doctrine, but also - for the sake of comparison and in order to find the best possible model for proceedings in this type of case - the solutions functioning in foreign legal systems (mainly German and French).